Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1079/bjn19870043
|View full text |Cite
|
Sign up to set email alerts
|

Methane excretion in the growing pig

Abstract: 1. Total methane excretion (CH, in breath+flatus) was measured in two experiments with thirty-six castrated male pigs (Danish Landrace) during the growth period from 20 to 120 kg live weight (LW). In Expt A, twenty-eight pigs were fed on a commercial diet alternately at high (HFL; metabolizable energy (ME) 1234 (SE 41) kJ/kg LW0'75) or low (LFL; ME 784 (SE 31) kJ/kg LW0'75) feed levels in different weight classes. In Expt B, eight pigs were constantly fed on a semi-purified diet at HFL without (-oil) or with 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 15 publications
5
28
1
Order By: Relevance
“…The effect of body weight was minor, however, significant in agreement with the studies by Christensen & Thorbek (1987) and Noblet & Shi (1994). However, Kirchgessner and coworkers concluded in a summary of several of their experiments that methanogenesis in pigs is fairly independent of live weight if feeding condition is kept constant.…”
Section: Influence Of Body Weight On Methane Emissionsupporting
confidence: 61%
See 2 more Smart Citations
“…The effect of body weight was minor, however, significant in agreement with the studies by Christensen & Thorbek (1987) and Noblet & Shi (1994). However, Kirchgessner and coworkers concluded in a summary of several of their experiments that methanogenesis in pigs is fairly independent of live weight if feeding condition is kept constant.…”
Section: Influence Of Body Weight On Methane Emissionsupporting
confidence: 61%
“…A reduced feed intake allow more time for fermentation and as a result more enteric CH 4 is produced as found by Christensen & Thorbek (1987) in a study with reduced feed intake to growing pigs. This could also be the case when adult sows in the dry period and during pregnancy are fed relative restricted (2-2.5 kg DM per day) in order not to gain excessive weight because this may cause health problems around farrowing and lactation.…”
Section: Comparison Between Growing Pigs and Adults Sows Fed Similar mentioning
confidence: 95%
See 1 more Smart Citation
“…It has been suggested that dietary fat, if it escapes pre-caecal digestion, might reduce the number of micro-organisms in rats. This was supported by data showing a reduced methane production in pigs receiving fat in their diets (Christensen & Thorbek, 1987). However, in a human study, Cummings et al (1978) found no effect of diets with high or low animal fat (62 or 152 g/d) on the relative numbers of faecal bacterial groups, including Enterobacteriaceae, Enterococcus, Bacteroides, lactobacilli and clostridia.…”
Section: Fatssupporting
confidence: 48%
“…More generally, methane production increases with pig body weight and DF level in the diet. The energy loss as methane would represent 5 to 10% of fermented energy (Christensen and Thorbek, 1984;Kirchgessner et al, 1987). The hydrogen production in pigs is rather low but very few measurements have been carried out (Jensen and Jorgensen, 1994).…”
Section: Me:de Ratiomentioning
confidence: 99%